Principles of scientific method: Notes on Lectures by Dr K.R. Popper given at the University of Otago, 22–26 May 1945; Lecture 6. Principle of indeterminacy - Popper, Karl (New Zealand Science Review, 2012)
​The question of indeterminacy is the most sensational [sic] in quantum theory. It really is one of the adventures of the mind. Werner Heisenberg found that deductively his equations led to a formula: that the consequence of lack of precise prediction leads to a statistical character, and that this statistical character is what is ultimately needed to explain the eigen-states of the atom. Erwin Schrödinger showed this with wave mechanics. Heisenberg said that as a consequence there are very few causal laws for atoms, which is, he said, a refutation of the principle of causality.